2018
DOI: 10.1186/s12960-018-0283-y
|View full text |Cite
|
Sign up to set email alerts
|

The trend of feminization of doctors’ workforce in Oman: is it a phenomenon that could rouse the health system?

Abstract: BackgroundParticipation of women in the medical profession over several countries worldwide was increased over the past decades. This paper is a part of ongoing studies aiming at addressing the issue of health workforce feminization among doctors in the Sultanate of Oman as well as exploring the health system readiness in dealing with this phenomenon.MethodsLiterature in addition to reports and records of the Ministry of Health, Oman (MoH), Sultan Qaboos University (SQU) and Oman Medical Specialty Board were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
4
30
0
Order By: Relevance
“…Appropriately, most women in our study sought formal help from a General Practitioner (GP) or a Gynecologist for their conditions. Ghana, like most countries, is undergoing a gender redistribution of the physician workforce [71][72][73][74]. The estimated 1:8,481 patient to provider ratio [75] has traditionally tipped in favor of male doctors [76][77][78][79], including Obstetric/Gynecologists (ObGyns) [80], even though there is ample literature to support the notion that women, particularly those in conservative cultures, prefer female OB-GYNs, given the intimacy of the services rendered by these providers [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately, most women in our study sought formal help from a General Practitioner (GP) or a Gynecologist for their conditions. Ghana, like most countries, is undergoing a gender redistribution of the physician workforce [71][72][73][74]. The estimated 1:8,481 patient to provider ratio [75] has traditionally tipped in favor of male doctors [76][77][78][79], including Obstetric/Gynecologists (ObGyns) [80], even though there is ample literature to support the notion that women, particularly those in conservative cultures, prefer female OB-GYNs, given the intimacy of the services rendered by these providers [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…Being a 'once-in-a-century pandemic', 29 some of the misgivings affecting HCWs include the fear of contracting a lethal virus and spreading it to the rest of their social network, lack of evidence-based prevention and intervention, lack of essential protective gear and the fact that the pandemic requires protracted shifts with a high volume of patients with different degrees of pathology and severity. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] This would imply that HCWs are now working in a uniquely hazardous situation and are thus vulnerable to stress and distress. In addition to operational stresses, some preliminary studies have suggested that psychosocial dysfunctions are rife among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…In our context, where gender divisions are more prominent, simply adopting standards and curriculums from other settings may mean that students are left deficient in exposure and skills. More effort is needed, particularly with the changes resulting from the ongoing feminisation [35] of the medical workforce, to ensure that all students are developing adequate skills and providing appropriate and full patient care.…”
Section: Discussionmentioning
confidence: 99%